1989
DOI: 10.1002/chin.198918215
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Pharmacological Activity of Stereoisomers of 1,4‐Dihydro‐2,6‐dimethyl‐4‐(3‐nitrophenyl)‐3,5‐pyridinedicarboxylic Acid Methyl 1‐(Phenylmethyl)‐3‐piperidinyl Ester.

Abstract: Esterification of the dihydropyridinedicarboxylic acid monoester (I) via the intermediate acid chloride with the piperidinol (II) gives the four diastereomers (III) ‐ (VI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Because the hepatic intrinsic clearance rate for (−)-alpha benidipine is greater than that for (+)-alpha benidipine, plasma concentrations of (+)-alpha benidipine are greater than those of (−)-alpha benidipine following the administration of a benidipine racemate to rats [5]. In addition, the hypotensive effect of (+)-alpha benidipine was between 30-and 100-fold the effect of (−)-alpha benidipine in spontaneously hypertensive rats [1]. The aforementioned observations suggest that the competitive metabolism of the stereoisomers of benidipine that follows the oral administration of the benidipine racemate gives rise to differential pharmacokinetics for the different enantiomers of benidipine.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Because the hepatic intrinsic clearance rate for (−)-alpha benidipine is greater than that for (+)-alpha benidipine, plasma concentrations of (+)-alpha benidipine are greater than those of (−)-alpha benidipine following the administration of a benidipine racemate to rats [5]. In addition, the hypotensive effect of (+)-alpha benidipine was between 30-and 100-fold the effect of (−)-alpha benidipine in spontaneously hypertensive rats [1]. The aforementioned observations suggest that the competitive metabolism of the stereoisomers of benidipine that follows the oral administration of the benidipine racemate gives rise to differential pharmacokinetics for the different enantiomers of benidipine.…”
Section: Introductionmentioning
confidence: 85%
“…In animal studies, the kinetic behavior and dynamic efficacies, respectively, of the benidipine stereoisomers were different [1][2][3][4]. Because the hepatic intrinsic clearance rate for (−)-alpha benidipine is greater than that for (+)-alpha benidipine, plasma concentrations of (+)-alpha benidipine are greater than those of (−)-alpha benidipine following the administration of a benidipine racemate to rats [5].…”
Section: Introductionmentioning
confidence: 99%
“…Benidipine, (S, S)-benidipine, (R, R)-benidipine, and amlodipine were synthesized in our laboratories as described (Arrowsmith et al, 1986;Muto et al, 1988). Efonidipine was extracted from tablets (Zeria, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The (ϩ)-␣ isomer was 30-to 100-fold more active than the (Ϫ)-␣ isomer in terms of the antihypertensive effect after i.v. administration to the spontaneously hypertensive rat (Muto et al, 1988).…”
mentioning
confidence: 98%
“…The (ϩ)-␣ isomer was 30-to 100-fold more active than the (Ϫ)-␣ isomer in terms of the antihypertensive effect after i.v. administration to the spontaneously hypertensive rat (Muto et al, 1988).Pharmacokinetic studies in rats (Kobayashi and Kobayashi, 1998) and humans (Kobayashi et al, 1997) have shown that benidipine is well absorbed but exhibits low absolute bioavailability as a result of marked first-pass metabolism. Accordingly, various metabolites were identified in these species (Kobayashi et al, 1997;Kobayashi and Kobayashi, 1998).…”
mentioning
confidence: 99%